A hemin binding G-quadruplex/Pb2+ complex to construct a visible light activated photoelectrochemical sensor on a ZnO/BiOI heterostructure. Issue 21 (13th October 2015) - Wang, Kewei; Sun, Na; Li, Xinpan; Zhang, Ruihua; Zu, Guangyue; Wang, Jine; Pei, Renjun
Abstract : The n-type ZnO nanorods and p-type BiOI nanoflakes were combined to form a p–n heterostructure for the development of rapid and sensitive visible light activated PEC sensors. Abstract : This study reported the development of a p–n heterojunction photoelectrochemical biosensor using a G-quadruplex as the recognition system. The n-type ZnO nanorods and p-type BiOI nanoflakes were combined to form the heterostructure by in situ growth of BiOI attributed to a simple impregnating-hydroxylation method. This simple p–n heterojunction fabrication method could facilitate the development of rapid and sensitive visible light activated PEC sensors. In this study, the ZnO/BiOI photoelectrode showed a rapid photocurrent decrease in the presence of Pb 2+ due to the electron withdrawing effect of hemin which bound with the G-quadruplex/Pb 2+ complex. This PEC biosensor exhibited a good response following the concentration of Pb 2+ in the range from 10 to 100 μM.